(untitled) (Czech Journal of International Relations, 1992)
The introductory part of the article engages in the character of COMECON, as an organization whose origin and function was conditioned not only by proper economic aspects but also (and de facto especially) by political, military, strategical and power ones. Stalin’s centralistic conception of economy control influenced even systemic and functional characteristics of the COMECON countries cooperation; the basic starting position can be expressed as a "mutual non-homogeneity" of their economies. It was connected with a non-function of their international market, with the absence of their own price systems and a generally accepted monetary equivalent, etc. (one can hardly differentiate the cause from the consequence). The part named "Market of the COMECON countries: slogan vs. reality" evaluates the efforts to overcome the problems by establishing a "common" or "single" market for the COMECON countries. It shows systematic as well material imperfections and follows the shift of opinions that was determined by developments of individual member countries. Another part, ,Reality of the realization", confronts the solution with adequate impacts on the mutual relations of the COMECON countries. As special attention has been paid to the USSR-Czechoslovakia relation; a , redistribution of advantages". A fundamental determinant of further development consists of the USSR political and economic collapses and the aim of its prior satellites to enter the Western European Community. It means an uncontrolled internal as well external changes for the mutual relations of. these countries which are still solving their existing "non-homogeneity". However, it comes at a time of considerable disruption of their economies and their mutual relations.